Study on the extent of removal of copper, zinc, iron, lead, and chromium ions in tap water by tea leaves - Hj. Suaidi, Noor Asyikin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2007)
It has been suggested that tea bags and tea leaves are capable of removing certain amowtt of heavy metals from water~ based on a study conducted using the coffee grounds. A study on the extent of removal of copper, zinc, lead, iron, and chromium ions from tap water using different types of tea leaves has been demonstrated. Tap water is known to contain certain level of concentration of these metals. The concentrations of copper, zinc, lead, iron, and chromium in the tap water from selected sources were detennined by atomic absorption spectrometer (AAS). Using the same tap water, tea extmcts were obtained by preparing tea using selected tea leaves. The extracts were subjected to acid digestion before being analyzed using AAS for the above metals. The concentrations of copper, zinc, lead, iron~ and chromium before and after preparation of tea were compared. Certain amount of the metals of concern was expected to be removed after tea preparation. Results from analysis demonstrated that tea bags removed copper, zinc and lead from the tap water by 29.0%, 31.3%, and 46.7% respectively. Large tea leaves, the oolong tea has been shown to remove copper, zinc, and lead by 54.0%, 48.0%, and 37.7% respectively. Fine tea leaves, namely the Ceylon tea removed the above metals by 20.3%, 42.0o/~ and 41.0% respectively. The concentration of iron and chromium were increased after tea extract preparation. Iron concentrations were increased by 0.190 ppm, 0.205 ppm, and 0.237 ppm in the tea bags, the large tea leaves, and the fine tea leaves respectively, whereas the concentrations of chromium were increased in tea bags, the large tea leaves, and the fine tea leaves by 46.0 ppb, 37.0 ppb, and 43.7 ppb respectively.